Chemical concentration of metal and rare reath elements (REE) in manganese nodules and crusts - Glasby, Geoffrey P (PANGAEA, 2023)
Manganese nodules and crusts samples analyzed in this work were chosen to represent a range of marine environments both oceanic and epicontinental. They were analysed by atomic-absorption spectrometry and optical-emission spectrometry to display a range of chemical compositions.
Keywords: Geochemistry; manganese micronodule; manganese nodule; ocean; sediment